2003
DOI: 10.1093/ageing/afg088
|View full text |Cite
|
Sign up to set email alerts
|

The combination of cognitive testing and an informant questionnaire in screening for dementia

Abstract: The combination of cognitive testing and an informant report according to a weighted sum rule in this population did not result in any advantage over the use of the Mini-Mental State Examination alone. The mixed results of this study contrast with those of Mackinnon and Mulligan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 14 publications
6
35
0
1
Order By: Relevance
“…In addition, the combined use of these tests did not increase the aforementioned diagnostic properties. Our results are in accordance with previously published studies in which these tests used alone or in combination in the screening for dementia, 17 but are in disagreement with a recent publication by Isella et al, 18 who suggested that the IQCODE had a good discriminative power between cognitively unimpaired older adults and patients with MCI. In this study, with similar cutoff values (28 for the MMSE and 3.19 for the IQCODE), both tests had a similar discriminative accuracy, but higher than in the current sample (AUC: 0.86 and 0.84, respectively).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, the combined use of these tests did not increase the aforementioned diagnostic properties. Our results are in accordance with previously published studies in which these tests used alone or in combination in the screening for dementia, 17 but are in disagreement with a recent publication by Isella et al, 18 who suggested that the IQCODE had a good discriminative power between cognitively unimpaired older adults and patients with MCI. In this study, with similar cutoff values (28 for the MMSE and 3.19 for the IQCODE), both tests had a similar discriminative accuracy, but higher than in the current sample (AUC: 0.86 and 0.84, respectively).…”
Section: Discussionsupporting
confidence: 75%
“…however, combining the MMSE and the IQCODE with the logistic regression did not result in any improvement over the use of the MMSE alone, contrasting with the previous studies presented. The authors discussed that perhaps in samples with lower dementia prevalence rates as in general practice (or in community samples) the weighted sum might be of greater utility 25 , as we found in the present report.…”
Section: Discussionsupporting
confidence: 58%
“…Investigating the same strategy (combining MMSE and IQCODE), 323 patients were assessed at a memory clinic 25 . The sample had a high prevalence of dementia (70.9%), and 31% had left school at the age of 16 and older.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to previous studies with elderly populations. 36,37 Although some of the currently used cognitive screening tests yield good results for recognizing subjects with MCI, they still have important limitations, mainly because they were designed for the diagnosis of established dementia, not of its prodromal and milder manifestations. Therefore, it is important to develop new, more specific tools to tackle the challenge of identifying, with high accuracy, subjects with mild cognitive deficits.…”
Section: Epidemiological Characteristics Of MCI In the Elderlymentioning
confidence: 99%